PARALINGUISTIC ASPECTS OF PUBLIC SPEAKING AND PRESENTATION SKILLS (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the paralinguistic aspects of public speaking and presentation skills. It analyzes the role of nonverbal communication elements such as intonation, voice tone, facial expressions, gestures, eye contact, pauses, and body language in enhancing the effectiveness of public speech. The study highlights that paralinguistic features significantly influence audience perception, emotional impact, and the overall success of presentations. Particular attention is paid to the importance of mastering paralinguistic competence in educational, professional, and intercultural communication contexts. The article concludes that effective use of paralinguistic means contributes to improving communication skills, increasing speaker confidence, and ensuring successful interaction with audiences.